Pengaruh Suku Bunga, Nilai Tukar, Inflasi Dan PDB Terhadap Harga Saham Perusahaan Sektor Energi Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Sinurat, Yenni Mariani; Sagala, Yomeini Margareth; Suryaman, Restu A (Accounting Progress, 2024)
This study aims to test and analyze the influence of interest rates, exchange rates, inflation and GDP on the stock prices of energy sector companies listed on the Indonesia Stock Exchange. The data used is time series data for 2018-2022, the analysis technique used is panel data regression analysis with the help of the E-views 11 program. The sample determination method used in this study is by using the purposive sampling method of 12 companies engaged in the energy sector. Based on the results, it shows that partially the Interest Rate has no effect and is not significant to the stock price. The Exchange Rate has no effect and is not significant to the Stock Price. Inflation has no effect and is not significant to the Stock Price. GDP has no effect and is not significant on the stock price. Simultaneously Interest Rates, Exchange Rates, Inflation and GDP have no effect and are not significant on stock prices.